Risk of Incidence and Lethality by Etiology of Severe Acute Respiratory Syndrome in Hospitalized Children Under 1 Year of Age in Brazil in 2024: A Cross-Sectional Study - Tamires de Nazaré Soares; Natasha Cristina Oliveira Andrade; Suziane do Socorro dos Santos; Marcela Raíssa Asevedo Dergan; Karina Faine Freitas Takeda; Jully Greyce Freitas de Paula Ramalho; Luany Rafaele da Conceição Cruz; Perla Katheleen Valente Corrêa; Marli de Oliveira Almeida; Joyce dos Santos Freitas; Wilker Alves Silva; Marcos Jessé Abrahão Silva; et al. (Tropical Medicine and Infectious Disease, 2025)
Severe Acute Respiratory Syndrome (SARS) represents a significant cause of morbidity and mortality in children under one year of age, a particularly vulnerable population due to immunological and respiratory immaturity. The diverse etiology includes multiple respiratory viruses such as Respiratory Syncytial Virus (RSV), influenza, rhinovirus, and SARS-CoV-2, each with distinct potential to cause severe illness and death. Understanding the specific incidence and lethality by etiological agents in the recent Brazilian context (2024), after the COVID-19 pandemic, is essential to guide surveillance and public health strategies. This study aimed to analyze the risk of incidence and lethality by specific etiology of SARS in children under one year of age hospitalized in Brazil during the year 2024. A descriptive cross-sectional study was performed using secondary data from the 2024 Influenza Epidemiological Surveillance Information System (SIVEP-Gripe), obtained via OpenDataSUS. Reported cases of SARS hospitalized in children <1 year of age in Brazil were included. Distribution by final classification and epidemiological week (EW) was analyzed; the incidence rate by Federative Unit (FU) (cases/100,000 < 1 year) with risk classification (Low/Moderate/High) was assessed; and, for cases with positive viral RT-PCR, the etiological frequency and virus-specific lethality rate (deaths/total cases of etiology ×100), also with risk classification, were extracted. A multivariate logistic regression model was performed for the risk factors of death. A total of 66,170 cases of SARS were reported in children under 1 year old (national incidence: 2663/100,000), with a seasonal peak between April and May. The majority of cases were classified as “SARS due to another respiratory virus” (49.06%) or “unspecified” (37.46%). Among 36,009 cases with positive RT-PCR, RSV (50.06%) and rhinovirus (26.97%) were the most frequent. The overall lethality in RT-PCR-positive cases was 1.28%. Viruses such as parainfluenza 4 (8.57%), influenza B (2.86%), parainfluenza 3 (2.49%), and SARS-CoV-2 (2.47%) had higher lethality. The multivariate model identified parainfluenza 4 (OR = 6.806), chronic kidney disease (OR = 3.820), immunodeficiency (OR = 3.680), Down Syndrome (OR = 3.590), heart disease (OR = 3.129), neurological disease (OR = 2.250), low O2 saturation (OR = 1.758), SARS-CoV-2 (OR = 1.569) and respiratory distress (OR = 1.390) as risk factors for death. Cough (OR = 0.477) and RSV (OR = 0.736) were associated with a lower chance of death. The model had good calibration (Hosmer–Lemeshow p = 0.693) and overall significance (p < 0.001). SARS represented a substantial burden of hospitalizations, with marked seasonal and geographic patterns. RSV and rhinovirus were the main agents responsible for the volume of confirmed cases but had a relatively low to moderate risk of lethality. In contrast, less frequent viruses such as parainfluenza 4, influenza B, parainfluenza 3, and SARS-CoV-2 were associated with a significantly higher risk of death. These findings highlight the importance of dissociating frequency from lethality and reinforce the need to strengthen etiological surveillance, improve diagnosis, and direct preventive strategies (such as immunizations) considering the specific risk of each pathogen for this vulnerable population.